Cutaneous angiosarcoma: A review of current evidence for treatment with checkpoint inhibitors - Guan, Lucy; Palmeri, Marisa; Groisberg, Roman (Frontiers in Medicine, 2023)
Cutaneous angiosarcoma (cAS) is a rare and aggressive subtype of soft tissue sarcoma with poor prognosis and suboptimal treatment options. Clinical presentation is variable, but cAS often arises from the head and neck. The most widely accepted current approach, surgical excision with adjuvant radiotherapy, is associated with high recurrence rates and can leave patients with profound disfigurement. Chemotherapy and targeted therapy alternatives have had limited success. Thus, there is a significant unmet need to address the absence of durable treatments for advanced and metastatic cAS. Like melanoma and cutaneous squamous cell carcinoma, tumor types with known response to immunotherapy, cAS harbors immune biomarkers such as tumor mutational burden high (TMB-H), PD-L1 positivity, ultraviolet signature expression, and tertiary lymphoid structures. While data on the use and efficacy of immunotherapy in cAS is limited, the biomarkers suggest a promising advancement in future treatment options. This review aims to summarize and discuss current data from case reports, case series, retrospective studies and clinical trials regarding immunotherapy treatment and outcomes for cAS.